2006
DOI: 10.5424/sjar/2006041-180
|View full text |Cite
|
Sign up to set email alerts
|

Improving soil surface properties: a driving force for conservation tillage under semi-arid conditions

Abstract: The effect of long term conservation tillage (CT) application on soil organic carbon (SOC) concentration, and on stratification ratios (SR) of SOC, soluble organic carbon (SOCs), microbial biomass carbon (MBC) and protease activity (PA) has been studied. The SR was established dividing values of these variables at 0-5 cm depth by values at 10-25 cm depth. The results were compared with those obtained under traditional tillage (TT). The study was conducted in a wheat-sunflower crop rotation established in 1991 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This requires the development of indicators characterizing this system; these indicators cannot be the same ones used in conventional agriculture. Suitable indicators of conservation tillage are required (Murillo et al, 2006). In our case, AC was the only soil property that showed a significant increase in the topsoil in both trials, with a significantly greater stratification ratio under conservation tillage than under traditional tillage.…”
Section: Discussionmentioning
confidence: 55%
“…This requires the development of indicators characterizing this system; these indicators cannot be the same ones used in conventional agriculture. Suitable indicators of conservation tillage are required (Murillo et al, 2006). In our case, AC was the only soil property that showed a significant increase in the topsoil in both trials, with a significantly greater stratification ratio under conservation tillage than under traditional tillage.…”
Section: Discussionmentioning
confidence: 55%
“…This C pool represents a high stratification ratio under resident vegetation because the soil remained permanently undisturbed throughout the cultivation cycle; on the contrary, in BV, the stratification ratio of POC decreased due to the soil tillage when the cover crop was resown (as indicated above). With respect to the stratification ratios of WSC and PMN, Murillo et al (2006) and Madejón et al (2007Madejón et al ( , 2009) also reported significant increases of the WSC stratification ratio with no tillage under semiarid climatic conditions in Spain; a greater stratification ratio for PMN under no tillage was described by Franzluebbers (2002), and Soon et al (2007a, b). However, in later cases SOC fractions showed lower values of stratification than POC.…”
Section: Discussionmentioning
confidence: 90%
“…Improving deep SOC content is an important part of improving soil quality. Previous study thought degree of stratification of SOC pools expressed as a ratio of soil depth could partly represent soil quality (Murillo, Moreno, Madejon, Giron, & Pelegrin, ). Thus, we must thoroughly analyze the SOC stratification ratio with different soil layers.…”
Section: Resultsmentioning
confidence: 99%